Efficient Qubit Routing for a Globally Connected Trapped Ion Quantum Computer. Issue 8 (7th July 2020) - Webber, Mark; Herbert, Steven; Weidt, Sebastian; Hensinger, Winfried K.
Abstract: The cost of enabling connectivity in noisy intermediate‐scale quantum (NISQ) devices is an important factor in determining computational power. A qubit routing algorithm is created, which enables efficient global connectivity in a previously proposed trapped ion quantum computing architecture. The routing algorithm is characterized by comparison against both a strict lower bound, and a positional swap based routing algorithm. An error model is proposed, which can be used to estimate the achievable circuit depth and quantum volume of the device as a function of experimental parameters. A new metric based on quantum volume, but with native two‐qubit gates, is used to assess the cost of connectivity relative to the upper bound of free, all to all connectivity. The metric is also used to assess a square‐grid superconducting device. These two architectures are compared and it is found that for the shuttling parameters used, the trapped ion design has a substantially lower cost associated with connectivity. Abstract : The cost of enabling connectivity in noisy intermediate‐scale quantum (NISQ) devices is an important factor in determining computational power. A particular architecture for trapped‐ion quantum computing relies on shuttling ions. An efficient ion routing algorithm is created along with an appropriate error model, which can be used to estimate the achievable circuit depth and quantum volume as a function of experimental parameters.